Analysis of digital-based sustainable fishermen cooperative risk management in Pangandaran Regency - Ashshiddiqi, Muhammad Taufan; Bukhori, Reza Fauzi; Desembriani, Helsa; Rohmat, Fahmi Hidayatul (Journal of Islamic Economics Lariba, 2024)
IntroductionFishermen's cooperatives face various external challenges such as fish price fluctuations, climate change and environmental damage.ObjectivesThis research analyzes the risk management of digital-based fishing cooperatives in Pangandaran Regency in the context of implementing the Blue Economy.MethodThis research uses a mixed methods approach with a sequential explanatory design. Quantitative data was obtained through a survey of 233 members of the Minasari Village Unit Cooperative (Koperasi Unit Desa abbreviated KUD in Bahasa Indonesia), while qualitative data was collected through interviews and case studies.ResultsThe research results show that the implementation of a cloud computing-based Management Information System (MIS) has the potential to strengthen risk management and support better governance in cooperatives.ImplicationsMIS can also increase transparency and operational efficiency, support the implementation of Blue Economy principles, and encourage the long-term sustainability of cooperatives through real-time data management and system integration.Originality/Novelty This study contributes to studies on digitalization of cooperatives to strengthen adaptation to complex environmental and economic challenges in the digital era.